2022
DOI: 10.3389/fmed.2022.911205
|View full text |Cite
|
Sign up to set email alerts
|

Short-term blood pressure variability and outcomes in non-dialysis chronic kidney disease

Abstract: BackgroundBlood pressure variability (BPV) is associated with cardiovascular and all-cause mortality, and has been demonstrated in dialysis patients, but has been poorly studied and remains controversial in non-dialysis chronic kidney disease (CKD) patients. We investigated the effect of short-term BPV on prognosis in this population.MethodsA total of 245 stage 1–4 CKD patients with 24-h ambulatory blood pressure recordings were recruited. BPV was evaluated by standard deviation, coefficient of variation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Blood pressure variability plays a crucial role in organ perfusion, and its correlation with prognosis has been observed in various diseases [ 27–33 ], including AIS [ 34 ]. Studies have indicated that following intravenous thrombolysis, there is an increase in blood pressure variability within the first 24 h, which can contribute to early and severe bleeding conversion in intravenous thrombolysis patients, thereby elevating the risk of poor prognosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure variability plays a crucial role in organ perfusion, and its correlation with prognosis has been observed in various diseases [ 27–33 ], including AIS [ 34 ]. Studies have indicated that following intravenous thrombolysis, there is an increase in blood pressure variability within the first 24 h, which can contribute to early and severe bleeding conversion in intravenous thrombolysis patients, thereby elevating the risk of poor prognosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang G et al, in their study of 245 non-dialyzed patients of renal failure (grade 1-4), found a correlation of high BPV (assessed by SD, CV, and VIM) with the progression of renal disease (seen only in unadjusted model and not in fully adjusted model) and cardiovascular disease but not with total mortality. 43 They found hyperkalemia, LV end-diastolic diameter, hypertension, and BMI as markers of high BPV.…”
Section: Blood Pressure Variability As a Prognostic Markermentioning
confidence: 98%